2004
DOI: 10.1016/j.bbamem.2004.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-permeabilizing activities of amphidinol 3, polyene-polyhydroxy antifungal from a marine dinoflagellate

Abstract: Amphidinols, which are polyene-polyhydroxy metabolites produced by the marine dinoflagellate Amphidinium klebsii, possess potent antifungal and hemolytic activities. The membrane permeabilizing actions of amphidinol 3, the most potent homologue, were compared with those of polyene antibiotics, amphotericin B (AmB) and filipin, in hemolytic tests, 23Na nuclear magnetic resonance (NMR)-based membrane permeabilizing assays, and UV spectroscopy for liposome-bound forms. In Na+ flux experiments using large unilamel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 38 publications
4
49
0
Order By: Relevance
“…3). All these findings together with previous results 116 may lead to a hypothetical molecular mode of action for AMs: (a) binding to the bi- layer membrane containing sterols chiefly with the polyolefin region (the C52 moiety) and the membrane affinity is heavily dependent on the length of the polyolefinic chain; (b) the center region (the C20-C51 moiety) takes a hairpin-shaped conformation, which is stabilized by a hydrogen-bond network in amphipathic environments, and (c) the flexible polyhydroxy region (the C1-C20 moiety) acts as a lining of ion-permeable ion channels.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…3). All these findings together with previous results 116 may lead to a hypothetical molecular mode of action for AMs: (a) binding to the bi- layer membrane containing sterols chiefly with the polyolefin region (the C52 moiety) and the membrane affinity is heavily dependent on the length of the polyolefinic chain; (b) the center region (the C20-C51 moiety) takes a hairpin-shaped conformation, which is stabilized by a hydrogen-bond network in amphipathic environments, and (c) the flexible polyhydroxy region (the C1-C20 moiety) acts as a lining of ion-permeable ion channels.…”
supporting
confidence: 58%
“…[113][114][115] On the other hand, the size of pores/lesions in erythrocyte membranes were estimated to be 2.0-2.9 nm in diameter, which is significantly larger than that of amphotericin B, 0.8 nm. 116 SDS micelles are reported to adequately mimic the amphipathic nature of a bilayer membrane even for a conformationally sensitive peptide such as gramicidin A. 114 Thus, the conformation of membrane-bound AM was deduced on the basis of NMR data obtained in SDS micelles.…”
Section: Activity-relevant Conformation and Bimolecular Interactions mentioning
confidence: 99%
“…In erythrocyte membranes, the sizes of channels were evaluated by osmotic protection experiments. [4][5][6] In these experiments, glucose passed through channels formed by amphotericin B and nystatin, [4][5][6] which were significantly different from the results of planar membranes showing impermeability to glucose. In the present study, we also observed that amphotericin B and nystatin made channels, allowing glucose to be permeable.…”
Section: Implication Of the Present Results For Determining Channel Smentioning
confidence: 85%
“…To test this possibility, we determined the channel sizes of polyene antibiotics, amphotericin B and nystatin, because these sizes formed in erythrocyte membranes have been reported to be roughly between radii of 0.36 and 0.46 nm, using sugars as protectants. [4][5][6] To verify the osmotic cell lysis process in this study, we simultaneously monitored the time courses of hemolysis and K + efflux from sheep erythrocytes induced by amphotericin B, by combining a fiber-optic spectrometer with a K + -selective electrode.…”
Section: Introductionmentioning
confidence: 99%
“…The only exception is maitotoxin with a molecular mass of 3422 g mol -1 , the largest non-biopolymer natural product known (Murata et al, 1994). Karlotoxins from the dinoflagellate Karlodinium veneficum (Bachvaroff et al, 2008;Van Wagoner et al, 2008) as well as amphidinols from Amphidium klebsii (Houdai et al, 2004;Houdai et al, 2005) have a similar mass range of about 1300 Da and membrane disruptive properties. These compounds form hairpin structures suggested to be important for the interaction with lipid bilayers of biomembranes.…”
Section: Unique Masses Found In Spe Fractionsmentioning
confidence: 99%